Use of PEGylated Recombinant Human Growth Hormone in Chinese Children with Growth Hormone Deficiency: A 24-Month Follow-Up Study - Yu Qiao; Zengmin Wang; Jinyan Han; Guimei Li (International Journal of Endocrinology)
Objective. Once-weekly PEGylated recombinant human growth hormone (rhGH) is the sole long-acting GH formulation available currently for pediatric patients with GH deficiency (GHD). The aim of this study was to evaluate the efficacy and safety of PEGylated rhGH therapy compared to daily rhGH therapy in GHD children treated for two years. Methods. A total of 98 children (49 children for the PEGylated rhGH group and 49 children for the daily rhGH group) with GHD were enrolled in this single-center, prospective, nonrandomized cohort study. PEGylated rhGH or daily rhGH was administered for 2 years. Height, height SDS, height velocity (HV), IGF-1, bone age (BA), and adverse events were determined throughout the treatment. Results. HV significantly increased over the baseline and was similar in both groups. In the PEGylated rhGH cohort, the mean ± SD HV was improved from 3.78 ± 0.78 cm/y at the baseline to 12.44 ± 3.80 cm/y at month 3, to 11.50 ± 3.01 cm/y at month 6, to 11.00 ± 2.32 cm/y at month 12, and finally 10.08 ± 2.12 cm/y at month 24 in the PEGylated rhGH group. In the daily rhGH group, HV was 3.36 ± 1.00 cm/y at baseline, increasing to 12.56 ± 3.71 cm/y at month 3, to 11.82 ± 2.63 cm/y at month 6, to 10.46 ± 1.78 cm/y at month 12, and to 9.28 ± 1.22 cm/y at month 24. No serious adverse event related to PEGylated rhGH or daily rhGH occurred during the 24-month study. Conclusion. PEGylated rhGH replacement therapy is effective and safe in pediatric patients with GHD. The adherence to once-weekly PEGylated rhGH therapy is superior to daily rhGH in children with GHD.